Adaptable Healing Patient Room for Stroke Patients - Daemen, E. M. L.; Flinsenberg, I. C. M.; van Loenen, E. J.; Cuppen, R. P. G.; Rajae-Joordens, R. J. E. (Methods of Information in Medicine, 2014)
Introduction: This article is part of the Focus Theme of Methods of Information in Medicine on “Pervasive Intelligent Technologies for Health”.Background: This paper addresses the evaluation with hospital staff of an in-patient environment that supports patients, family, nursing staff and medical specialists during the recovery process of neurology patients and especially patients recovering from a stroke. We describe the methods that were used to evaluate the Adaptive Daily Rhythm Atmospheres (ADRA), Artificial Skylight (AS) and Adaptive Stimulus Dosage (ASD) concepts.Objectives: The goal of this evaluation was to gather qualitative and quantitative feedback from hospital staff about the usefulness, the usability and desirability of the Adaptive Daily Rhythm Atmospheres (ADRA), Artificial Skylight (AS) and Adaptive Stimulus Dosage (ASD) concepts that were implemented as different phases of a novel healing patient room. This paper reports the effects of these concepts with regard to 1) the healing process of the patient and 2) the workflow of the staff. These results are part of a larger R&D project and provide the initial feedback in an iterative user-centered design methodology.Methods: After signing informed consents, the group of participants was taken to the laboratory environment where they were introduced to the Adaptive Healing Environment Patient Room and where they could also experience the room. Then, the participants were seated next to the patient bed so they had a similar viewing angle as the patients. The participants received a booklet with questionnaires. The items on this questionnaire addressed the influence on the healing process (i.e., the possible effect the concept/phase has on the healing process of the patient, meaning faster recovery, better sleep and enhanced well-being) and influence on the workflow (i.e., the possible effect of such a concept/ phase on the working activities of the staff in the ward). We presented every concept (AS and ASD) and all the phases of ADRA. After every presentation of the concept or phase of the ADRA system the participants rated the concept or phase anonymously on a 7-point Likert scale. In addition to rating the phase in the therefore designed booklets, they were also asked to motivate their ratings in writing. Subsequently, a focus group discussion took place. During the discussion the two note takers wrote down all the comments. Afterwards the quantitative results were analyzed with the non-parametric Kruskal-Wallis test. Significant effects were further analyzed in a post-hoc Mann-Whitney test.Results: The results show that hospital staff expects a positive effect on the healing process of the patient for the Artificial Skylight, the Adaptable Stimulus Dosage concept and the different ADRA phases that provide a clear daily rhythm structure during the day. In fact the staff members from different healthcare institutions and with different professional roles agreed on most aspects. In addition, the staff also expected a positive effect for almost all phases on the efficiency of the clinical workflow, also for the AS and ASD concepts. This is a very promising result as the phases were designed primarily with the healing effect of the patient in mind.Conclusions: The hospital staff evaluation in the laboratory setting gave us an indication of the likely impact of the Adaptive Healing Environment Patient Room on the healing progress of patients. Furthermore, this laboratory evaluation of the concepts was an important step that enabled to improve the shortcomings of the current concept before starting clinical trials. In addition, we generated feedback from different departments from different institutions, which suggest that they all see similar added values for the patient room
Keywords: Adaptive systems; user experience evaluation; stroke; healing environments; patient room